Temperature estimation of inflamed bowel by the photoacoustic inverse approach. (10th January 2020) - Alaeian, Mohsen; Orlande, Helcio R. B.; Machado, João Carlos
Abstract: Local temperature increase is one of the five classical signs of regions with inflammations. This work is focused on the application of the photoacoustic technique for the estimation of the temperature field in the colon, as the solution of an inverse problem, for the detection of inflamed regions. Two‐dimensional cases are examined here involving a cross section of the bowel, which characterize either the inflammation of the whole mucosa layer, or three small inflamed regions. The inverse problem is solved for a rotating laser inside the intestine lumen, which imposes pulses for the generation of the acoustic waves. One single ultrasound detector, also located at the laser rotating shaft, provides the simulated measurements for the inverse analysis. The inverse problem is solved here with the minimization of the maximum a posteriori objective function. Results show that the proposed technique can be applied for accurate estimations of the temperature distribution in the region of interest, which might be used for the diagnosis of inflammatory bowel diseases (IBD). Abstract : The figure shows the estimation of three inflamed regions in the bowel mucosa, which are characterized by temperatures higher than those of the other regions. The inverse problem was solved with simulated photoacoustic measurements. HIGHLIGHTS: The photoacoustic inverse approach was applied to estimate the temperature in the bowel wall, by using numerically simulated measurements, aiming at the identification of inflamed regions at large temperatures. The laser and the ultrasound transducer were assumed at the tip of a rotating shaft, which was inserted in the intestine lumen via a catheter. No a priori knowledge regarding the existence of an inflamed region was initially considered for the solution of the inverse problem. The posterior probability distributions in the inflamed regions were correctly centered at the high temperatures and exhibited small variances, thus demonstrating that the technique advanced in this work might be applicable in the future for the diagnostic of inflammatory bowel diseases (IBD).